Identification of Science Literacy Ability of MAN 1 East Lombok Students in Learning Static Fluid Matter Physics - Muh Wahyudi; m kafrawi (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2022)
This study aims to obtain an overview of the science literacy ability of MAN 1 East Lombok students in learning static fluid matter physics. This type of research is quantitative-descriptive research. The instrument used was a static fluid matter science literacy PG question totaling 20 questions. The sample in this study was class XI science three students totaling 34 students. The results showed that the science literacy ability of MAN 1 East Lombok students in learning static fluid matter physics were classified as a high category with an average percentage of 73.08%. While the ability based on competence to identify scientific problems, with an average rate of 90.20% of the type, is very high, in the competence to explain phenomena scientifically, with an average percentage of 70.22% of the high category, while in competence using scientific evidence with an average rate of 58.82% of the standard type.